2019
DOI: 10.3390/ijerph16071284
|View full text |Cite
|
Sign up to set email alerts
|

Going beyond Quietness: Determining the Emotionally Restorative Effect of Acoustic Environments in Urban Open Public Spaces

Abstract: The capacity of natural settings to promote psychological restoration has attracted increasing research attention, especially with regards to the visual dimension. However, there is a need to extend these studies to urban settings, such as squares, parks or gardens, due to the global trend towards urbanisation, and to integrate the dimension of sound into landscape. Such was the main aim of this study, in which 53 participants assessed four public spaces in Vitoria-Gasteiz (Spain) as part of the CITI-SENSE Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 45 publications
4
23
0
Order By: Relevance
“…Audio-visual experiences were also positively correlated with psychological responses ( p < 0.05) with coefficient R ranging from 0.665–0.873 in Music Park. It can be concluded that, with audio-visual comfort increasing, the level of psychological responses, including CD, RA, EF, and FD, also increased, which was consistent with a recent research result in Spain [17].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Audio-visual experiences were also positively correlated with psychological responses ( p < 0.05) with coefficient R ranging from 0.665–0.873 in Music Park. It can be concluded that, with audio-visual comfort increasing, the level of psychological responses, including CD, RA, EF, and FD, also increased, which was consistent with a recent research result in Spain [17].…”
Section: Resultssupporting
confidence: 90%
“…In recent years, some studies have assessed the psychological recovery potential of soundscapes [8,13,14,15]. They focused on the relationship between the acoustic environment and psychological responses [16,17] and they identified the sound sources that promoted positive emotions (stress recovery) [13,18]. According to a study by Daniel Shepherd et al, the mean scores of psychological well-being described by the WHO’s short-form quality of life instrument (WHOQOL-BREF) perceived by residents in quiet areas were higher than in noisy areas [19].…”
Section: Introductionmentioning
confidence: 99%
“…These results are similar to those observed by Axelsson et al (2010) . According to Herranz-Pascual et al (2019) , the characteristics of the soundscape that contribute to well-being and the reduction of perceived stress are calm and tranquil. In this way, a positive affective response to natural open environments allows the individual to recover from fatigue and negative emotional states ( Ulrich, 1981 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is fair to assume that non-quiet spaces might still have the potential to promote positive user experiences of an urban environment, or that quietness cab not necessarily always match less "loud" acoustic environments. Herranz-Pascual and colleagues [12] indeed suggest that lively and vibrant urban soundscapes may also enhance people's restoration. Aletta and Kang [13] propose a model to predict urban "vibrancy" using a soundscape approach.…”
Section: Extending the Research Scope To More Soundscape Quality Dimementioning
confidence: 97%